Vprašanje človeške ustvarjalnosti v dobi UI - Rožman, Lucija (Bogoslovni vestnik, 2024)
Comparing the creativity of computer algorithms with human creativity calls into question the value of human creativity and at the same time creates a dualistic scheme of two antagonistic entities: man-machine. Whether AI really threatens human creativity depends on how we approach creativity, which is a very complex phenomenon due to its multidimensionality. The sciences outline two possible approaches: the approach of the empirical sciences establishes criteria (e.g. surprisingness, originality, novelty) by which creativity can be judged more easily, while the theological approach starts from the Creator's creative act and asks for a creative mode (Word, Breath, Freedom) that is relational. From a theological point of view, creativity is the essential definition of the person who is created in the image of God and who alone is free to respond to the Creator's calling precisely through creativity. In this sense, AI does not threaten human creativity, but it can serve as a tool and help it to develop further.
Keywords: artificial intelligence; Beseda; Breath; creative mode; creativity; criteria of creativity; Dih; kriteriji ustvarjalnosti; liberty; svoboda; umetna inteligenca; ustvarjalni način; ustvarjalnost; Word